Penerapan Pendidikan Karakter Siswa Sekolah Dasar Melalui Budaya Sekolah - Agi Hamdani; Dede Margo Irianto; Yeni Yuniarti (Universitas Muhammadiyah Kuningan, 2023)
This study aims to describe what character values ​​are applied through the implementation of school culture in SD Negeri Cinangerang I Sumedang. This study uses a qualitative method with a phenomenological study approach. The main data sources are school principals, teachers, and students. Meanwhile, supporting data is in the form of documentation of activities related to research studies. Data collection techniques through interviews, observation, and documentation. The validity of the data researchers used the method of source triangulation and media triangulation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of the study concluded that character education is carried out by applying school culture and good habituation through routine school activities and in the learning process in the classroom. Character values ​​developed are religious, responsible, independent, nationalism, caring for the environment. In the implementation there were several obstacles such as the lack of facilities and infrastructure, the presence of students who were less enthusiastic, and the presence of parents who did not care about school activities.